Developing and Evaluating a Capacity-Building Intervention for Healthcare Providers to Improve Communication Skills and Awareness of Hard of Hearing and D/deaf Populations: Protocol for a Participative Action Research-Based Study - Bodenmann, Patrick; Singy, Pascal; Kasztura, Miriam; Graells, Madison; Cantero, Odile; Morisod, Kevin; Malebranche, Mary; Smith, Pascal; Beyeler, Stéphane; Sebaï, Tanya; Grazioli, Véronique S. (Frontiers in Public Health, 2021)
Background D/deaf and hard of hearing populations are at higher risk for experiencing physical and mental health problems compared to hearing populations. In addition, they commonly encounter barriers to accessing and benefiting from health services, which largely stem from challenges they face in communicating with healthcare providers. Healthcare providers commonly lack tailored communication skills in caring for D/deaf/hard of hearing populations, which lead to difficulties and dissatisfaction for both staff and D/deaf/hard of hearing communities. This research project aims to develop and evaluate a capacity-building intervention for healthcare providers with the goal of increasing their awareness of D/deaf and hard of hearing individuals’ experiences with the healthcare system, their distinct needs, and improving their capacity to communicate effectively with this patient population. Methods This research project features a participative action research design using qualitative and quantitative methods. Consistent with participative action research, the study will actively involve the target populations, key stakeholders and representative associations. The intervention will be developed and tested through iterative phases. The Integrated Model of Training Evaluation and Effectiveness will guide prospective evaluation of the intervention. The latter will involve qualitative and quantitative assessments in participants before and after the intervention and at 6-months follow-up. Discussion Results will contribute to research aimed at decreasing barriers to accessing and benefiting from healthcare services for D/deaf and hard of hearing individuals. Findings will be presented to representative associations and political authorities, as well as disseminated at research conferences and in peer-reviewed journals.